2015
DOI: 10.4238/2015.december.21.41
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of microRNA-34a in esophageal squamous cell carcinoma

Abstract: ABSTRACT. has been found to be downregulated in esophageal squamous cell carcinoma (ESCC) tissues compared with that in normal tissues (P < 0.05), and miR-34a overexpression increased apoptosis and decreased clonogenic formation. However, the clinical significance and prognostic value of miR-34a in ESCC has not yet been investigated. In total, 111 patients with ESCC diagnosed and treated at the Department of Thoracic Surgery of Fujian Provincial Hospital between March 2008 and February 2014 were included in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
3
7
0
Order By: Relevance
“…Increasing evidence has shown that alterations in the expression of miRNAs are associated with the development, prognosis and survival rate of EC (18). Studies have reported the lack of expression of miR-34a in ESCC and colon cancer (19,20). Consistent with those reports, we demonstrated the down-regulation of miR-34a in ESCC patients compared with paired cancer-adjacent normal tissues.…”
Section: Discussionsupporting
confidence: 91%
“…Increasing evidence has shown that alterations in the expression of miRNAs are associated with the development, prognosis and survival rate of EC (18). Studies have reported the lack of expression of miR-34a in ESCC and colon cancer (19,20). Consistent with those reports, we demonstrated the down-regulation of miR-34a in ESCC patients compared with paired cancer-adjacent normal tissues.…”
Section: Discussionsupporting
confidence: 91%
“…It indicates that the mechanisms of miR-34a repression may be aberrant from the CpG methylation of its promoter in ESCC. Studies have found that miR-34a overexpression can suppress cell proliferation, migration, invasion, and EMT (22)(23)(24)(27)(28)(29)(30)(31)43). Furthermore, miR-34a has significant relationships with node metastases, clinical stage, and patient mortality in tongue squamous cell carcinoma (12) and ESCC (43).…”
Section: Discussionmentioning
confidence: 99%
“…MiR-34a is located in chromosome 1p36, which belongs to the tumor suppressor miR-34 cluster [ 36 ]. Some studies have reported that miR-34a lacks expression in human esophageal cancer, pancreatic cancer, colon cancer, and neuroblastoma [ 11 , 37 39 ], and that its low expression promotes tumor formation. We proved the relevance of miR-34a in clinical malignancies, that is, the low expression of miR-34a is significantly associated with advanced stages and lymph node metastasis in Kazakh ESCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…To date, many human endogenous miRNAs have been reported in the oncogenesis and progression of ESCC, such as miR-130b [ 8 ], miR-93 [ 9 ], and miR-183 [ 10 ]. MiR-34a is downregulated and correlated with lymph node status and advanced clinical stage in ESCC, and low miR-34a levels in the cancer cells in ESCC are associated with increased colony formation and decreased apoptotic [ 11 17 ]. However, the role of miR-34a is complicated and the investigation between miR-34a and ESCC are little.…”
Section: Introductionmentioning
confidence: 99%